A Needs Analysis of Inquiry-Based Virtual Laboratory for Acid–Base Titration - Rudi Purwanto; Manihar Situmorang; Ajat Sudrajat (Universitas Negeri Medan, 2025)
Traditional instructional methods, such as PowerPoint and video presentations, often fall short in promoting deep understanding and student engagement, particularly in complex topics like acid–base titration. This study investigates the need for innovative, inquiry-based learning resources integrated with virtual laboratories to support instructional improvement in analytical chemistry. A descriptive qualitative approach was used, involving in-depth interviews with a lecturer and a student, as well as questionnaires completed by 29 students. The findings reveal widespread dissatisfaction with current learning resources due to limitations in interactivity, completeness, and applicability. Most students strongly agreed on the need for enhanced instructional materials, inquiry-driven learning models, and simulation-based tools. A feasibility assessment of existing materials showed high scores in language clarity but highlighted the need for improvements in content quality and visual presentation. These results underscore the importance of combining guided inquiry with virtual laboratories to enhance conceptual understanding, engagement, and critical thinking. The study contributes practical insights for designing more effective learning environments in chemistry education, especially in settings with limited access to physical laboratory facilities.